2015
DOI: 10.1002/ajmg.a.37246
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mortality and morbidity according to gestational ages and birth weights in infants with trisomy 18

Abstract: The aim of this study was to clarify the effects of gestational age and birth weight on outcomes of the infants. Medical records of 36 infants with trisomy 18 admitted to Tokyo Women's Medical University Hospital from 1991 to 2012 were reviewed retrospectively. We compared clinical characteristics between term infants (n = 15) and preterm infants (n = 21). There were one very‐low‐birth‐weight (VLBW) term infant (5%) and 12 VLBW preterm infants (80%). Although there were no significant differences in clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Male gender, cardiovascular abnormalities, prematurity, and very low birth weight negatively affect survival. 6,8,24,28 In keeping with those studies, we found that survival rates were significantly lower in infants with birth weight of <2,000 g and who had more than two anomalies (p ¼ 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Male gender, cardiovascular abnormalities, prematurity, and very low birth weight negatively affect survival. 6,8,24,28 In keeping with those studies, we found that survival rates were significantly lower in infants with birth weight of <2,000 g and who had more than two anomalies (p ¼ 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…8,9 Median survival duration reported in term infants who received neonatal intensive care vary between 30 and 152 days, with 1-year survival rate in 25%. 6,8,17,27 Nonetheless, long-term outcomes have not been reported in infants who survived beyond 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In the most prevalent forms of CHD represented in T13 and T18, CHS may not be warranted in the neonatal period; however, the symptomatic burden of CHD often precipitates surgical intervention. Additionally, respiratory dysfunction and pulmonary abnormalities, which have been reported to be the cause of death in T18 for those <1 month of age, 27 are exacerbated by the presence of CHD. It is likely that removing the influence of even relatively simple forms of CHD on respiratory issues played a role in the improved survival-to-hospitaldischarge rate seen in our study.…”
Section: Figurementioning
confidence: 99%
“…infants with T-18 have greatly complex heart defects such a hypoplastic left heart syndrome and transposition of the great arteries (Baty, Blackburn, & Carey, 1994;Bruns & Martinez, 2015;Kavarana, 2016;Van Dyke & Allen, 1990). Heart failure secondary to an unrepaired cardiac defect is considered one of the major causes of deaths in infants with T-18 along with respiratory failure or central apnea (Cereda & Carey, 2012;Embleton et al, 1996;Imai et al, 2015).…”
mentioning
confidence: 99%